Physician’s Seeking Behaviours for Health Information Services for their Patients - Elena Link; Paula Memenga (European Journal of Health Communication (EJHC))
In addition to consultations, physicians can contribute to patients' knowledge and empowerment by referring them to appropriate health information services. This requires physicians to engage in health information-seeking behaviours to be aware of where to find adequate health information. Our study aims to deepen the understanding of physicians' intentions to seek health information services for their patients. The modelling of their seeking intent is guided by the Planned Risk Information Seeking Model adapted for physicians for the first time. An online survey of 364 German primary care physicians and specialists supports the utility of the psycho-motivational predictors considered in the PRISM for explaining physicians' seeking intent. Attitudes towards health information services, seeking-related subjective norms concerning colleagues, and perceived seeking control emerged as the most relevant predictors of physicians' seeking intent. These three predictors could form the ground for a parsimonious model of physicians' seeking intent and highlight barriers that need to be addressed to strengthen the navigational role of physicians.